Influence of low-level fall protein supplementation on forage intake, diet digestion, and selection by beef steers grazing tallgrass-prairie range - Donald A. Llewellyn; R.C. Cochran; T.T. Marston; C.G. Farmer; T.A. Wickersham (Kansas Agricultural Experiment Station Research Reports, 2003)
This study evaluated the effect on forage utilization of providing a limited quantity of a high-protein (40% crude protein) supplement to beef cattle grazing tallgrass prairie during the fall. Sixteen ruminally fistulated beef steers were randomly assigned to one of two treatments (fall supplementation or no fall supplementation), which were evaluated for their effect on forage intake and digestion during September and November. Within each treatment, four steers were used for measuring diet selection (by ruminal evacuation) and four were used for determining diet digestion (by total fecal collection). Data from both groups were used to calculate forage intake. Steers were individually fed a high-protein supplement at a rate of 0.14% of body weight/day (as-fed basis; 0.80 lb/day during September and 0.99 lb/day during November) but prorated and delivered only three days per week. Quality of diet selected decreased as season progressed (decreased protein and increased fiber) and, as a result, forage intake and digestion was significantly lower during the late fall period. Neither diet selection nor forage intake were significantly influenced by fall supplementation; however, supplemented steers digested their total diet to a greater extent.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Low-level fall protein supplementation; Forage intake; Diet digestion; Steers; Tallgrass-prairie range